Violence against Women during the Timurid Conquest (14th and 15th Centuries). The Devastating Account of Chronicler Arabshah - Carbó, Laura (Revista Melibea, 2024)
Ahmad b. Muhammad Ibn 'Arabshah (1392-1450) wrote The Wonders of Destiny of the Ravages of Timur, a biography completed in Damascus on 12 August 1435. This work, which is highly critical of Tamerlane’s management and conquests, is one of the most eloquent sources of information on both the nomadic women of his clan and the representatives of the conquered peoples. Females from all the subjugated communities, survivors of the massacres, were deported for agricultural work and moved to distant territories, indefinitely separated from their families. The representatives of the noble lineages guaranteed with their lives the pacts and served to give lineage to the warrior bands without prestige or nobility. This paper aims to list the historiographical resources used by the Arab author to expose the atrocities committed against women. Firstly, the account of the "wonders" of the Timurid advance, a sequence of acts of extreme force that surprised by their savagery and devastation. Secondly, the concatenation of political events permitted the rise of the network of power created around the women of the devastated territories. The primary hypothesis is that Arabshah uses the same historiographical axes as his pro-Timurid contemporaries, the military and the political, but with an opposite sign, considering the female role in this period of transitions.